Edukasi Kesehatan untuk Meningkatkan Pengetahuan Siswa dalam Pertolongan Pertama Kecelakaan Lalu lintas - Siregar, Latifah; Siregar, Nabilah; Pasaribu, Yohanna Adelina; Julianto, Julianto (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Traffic accidents are emergency events that often occur unexpectedly in society and can cause injury or death. Proper first aid for traffic accident victims is needed to help reduce mortality rates, further complications and improve healing in victims. Proper first aid in emergency conditions such as trauma accident victims needs to be based on good knowledge. This community service activity aims to improve students' knowledge in first aid for traffic accidents. This community service activity was carried out on 35 grade XII students at a high school in Perdagangan, Simalungun Regency. The results of this community service showed an increase in students' knowledge about first aid for accidents after being given health education. Health education about emergency handling is highly recommended to be given to the community as laypersons.